The Use of Semantic Mapping to Improve Vocabulary Comprehension - Thaledon, Sriphloi (HRD Journal, 2020)
Learning vocabulary is considered to be the most important aspect of second language acquisition (Knight, 1994). The purposes of this study were to investigate the effects of the semantic mapping technique on student vocabulary comprehension, and to examine the students’ attitudes towards the semantic mapping technique. The study employed a quasi-experimental research method with two groups (experimental and control). The experimental group learned vocabulary with the use of semantic mapping, while the control group learned with a traditional method. The data were analyzed by means, standard deviations, descriptive statistics, an independent t-test, and paired t-test. The participants of this study were 46 students selected from Vocational-3/1 majoring in computer business and Vocational-3/2 majoring in marketing. The results from comparing the pre-tests and post-tests of this study showed that the experimental group made higher improvement than the control group and the students had positive attitudes towards the semantic mapping technique.